Prognostic Factors and Nomogram for Malignant Brainstem Ependymoma: A Population‐Based Retrospective Surveillance, Epidemiology, and End Results Database Analysis - Xiaoyu Ji; Siyuan Yang; Dejing Cheng; Wenbo Zhao; Xuebo Sun; Fang Su (Cancer Medicine)
ABSTRACT Purpose This study aimed to identify prognostic factors and develop a nomogram for survival in patients with brainstem ependymoma. Methods Data of 652 patients diagnosed with brainstem ependymoma extracted from the Surveillance, Epidemiology, and End Results (SEER) registry from 2000 to 2020 were analyzed. Univariate and multivariable Cox regression analyses were performed to examine factors influencing overall survival (OS). Receiver operating characteristic curve (ROC) and calibration curves were used to verify the nomogram. The Kaplan–Meier method was used to analyze OS based on treatment methods stratification or different age patterns. Results Six independent prognostic factors of patients with brainstem ependymoma were identified, including age, race, marital status, radiation, gross total resection (GTR), and histology. A comprehensive nomogram model was developed utilizing these predictors identified through multivariable Cox regression analysis. Furthermore, we found that patients with GTR have improved overall survival than patient with no surgery and biopsy only or with partial resection (GTR vs. no: p = 0.0004, GTR vs. partial resection: p = 0.022). Patients with radiation have improved overall survival than patient without radiation (p = 0.00013). Patients with GTR combined radiation therapy have improved overall survival than patient without or with GTR or radiation therapy only (p < 0.0001). Different treatment methods have no significant difference in the overall survival probability of the elderly group. Conclusions Individuals who are Black and anaplastic ependymomas were negative risk factors for brainstem ependymoma associated with an increased risk of mortality. Patients aged < 50 years with GTR and radiation always had better survival.